Economics Of Vegetable Seed Production In chittur Taluk Of Palakkad District - Sandhya M Das (Department of Agricultural Economics, College of Horticulture, 2000)
The present study on "Economics of vegetable seed production in Chittur Taluk of Pa1akkad District" was conducted with the specific objective of evaluating its economics and identifying the problems. The study was undertaken during March-May 2000, and the data pertains to the year 1999. The production details of ten most important crops m the area (amaranthus, cucumber, chilli, bittergourd, okra, cowpea, pumpkin, snakegourd, ashgourd and brinjaJ) were gathered from the whole population of seed growers in the area by personal interview method using a pretested, structured questionnaire. The cost of cultivation (cost C1) ranged from the lowest Rs.29,514.95 in amaranthus to Rs.69,837.74 for chillies. Like in the case of most of the annual/seasonal crops in Kerala the major item of expenditure was human labour in all the crops except in amaranthus, pumpkin and ashgourd where it was manures and manuring. Manuring was proved to be the most expensive operation. While gross income realised was highest in chillies (Rs.l ,40,485.26) and lowest in okra (Rs.47,494.90) the cost of production was highest for snakegourd (Rs.23 1.68) and lowest for okra (Rs.61.17). Benefit cost ratio at cost C3 was found to be greater than one in all the crops studied. Amaranthus and cucumber seed production proved to be financially the most efficient enterprise. The germination tests conducted using the vegetable seed samples collected from the respondents revealed that all the samples conformed to the prescribed germination standards except in the case of pumpkin, ashgourd and brinjal. The major constraints experienced by the vegetable seed growers were also identified.